Characterization and arrangement of forests of pinyon pine (Pinus cembroides subsp. orizabensis) from the Eastern Mexican Basin (Puebla, Tlaxcala and Veracruz) - Granados Victorino, Ro Linx; Granados Sánchez, Diódoro; Sánchez-González, Arturo (Instituto de Ecología, A.C., 2016)
Pinus cembroides subsp. orizabensis is the pinyon pine with the more southern distribution in America; most of its populations develop into the limits of the “Cuenca Oriental”, the only cold semiarid area in Mexico, and they are distributed in at least five isolated localities. The objectives of present study were to carry out a floristic inventory and a structural analysis of pinyon pine forests, whose canopy is dominated by the taxon referred, in the “Cuenca Oriental”. The fieldwork was divided into the search and collection of specimens of vascular plants by standard techniques to further identify the specimens in the laboratory; and from sampling of forests to determine the density, coverage and importance value of species. Cluster analysis was used to estimate the similarity in species composition between forests; the relationship between environmental and environment and soil factors with respect to composition and distribution of species between localities was estimated by canonical correspondence analysis. Structural values of species were used for characterization of forests physiognomic. The results indicate that the pinyon pine forests develop on volcanic substrate, with a neutral or slightly basic pH (from 7 to 8), and they are found from 2300 m to 2700 m a.s.l. The main plant associations identified are: Pinyon-Nolina, Pinyon-Juniperus, and Pinyon-Pinus pseudostrobus; the taxa Pinus cembroides ssp. orizabensis and Nolina parviflora were constant in all the studied localities. The floristic composition of these forests is mainly related to the edaphic factors Ca, and N.